Perubahan Kedudukan Notaris Pengganti Pada Saat Notaris yang Diganti Meninggal Berdasarkan Undang-Undang Nomor 2 Tahun 2014 - Nurjanah, Siti (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2023)
This study aims to find out if a Notary applies for leave. The Notary must appoint a Substitute Notary to replace all of his authority. Still, if the Notary on leave dies, a different legal status will arise for the Substitute Notary, related to all powers, duties, and responsibilities to serve the community. At that time, there was a legal vacuum between the Notary who died before the leave ended and the Substitute Notary. A Substitute Notary will carry it out as a Notary Temporary Officer and must not be reappointed as a Substitute Notary as a Notary Temporary Acting. Thus, the Notary Temporary Officer can carry out what is under his authority within 30 days from the date the Notary dies, make a deed on behalf of a substitute Notary, and have a Notary protocol. All Notary Protocols must have been drawn up and Minutes of Substitute Notary Protocol submitted by the Notary Substitute within 60 days of the Notary's death; then all Protocols are submitted to the Notary Recipient of the protocol, then the Substitute Notary as temporary official Notary, Notary receiving Protocol and Regional Supervisory Board sign minutes of hand over. In this study, the authors used normative research methods.